MEWUJUDKAN TATA KELOLA PEMERINTAHAN DESA YANG BAIK MELALUI PENERAPAN AKUNTABILITAS SOSIAL - Dekki Umamur Ra'is (Journal of Urban Sociology, 2022)
The Village Law mandates village administration to realize good village governance. One indicator of the achievement of good village governance is the accountability of village government and the fulfillment of the rights of villagers. Accountability in practice has two mechanisms, namely vertical accountability and horizontal accountability. However, the two mechanisms are considered incapable of realizing good village governance because there are still loopholes for corrupt behavior in government. So there must be another mechanism, namely social accountability mechanisms. This study uses the method of a literature review. Data collection was carried out by extracting library sources that were relevant to the topic of study. Through the application of the principle of social accountability, village residents will be directly involved in supervising the administration of the village government and will hold them accountable for the policies and services that have been carried out by the village government. So that the application of social accountability can be a catalyst or tool in realizing good village governance.Keywords: Social Accountability; Good governance; Village Administration